Predictive value of percutaneous peripheral arterial compliance T in left ventricular diastolic function with coronary artery disease - Zhang, Wenhao; Liang, Guoliang; Lv, Liang; Gu, Xinxin; Zhang, Qiong; Liu, Ankang; Ma, Jiangwei (Frontiers in Cardiovascular Medicine, 2024)
BackgroundDiastolic dysfunction emerges early in patients with cardiac insufficiency and is prevalent, underscoring the importance of its early identification and intervention in the prevention of heart failure. The study leverages the convenience and accuracy of measuring peripheral arterial sclerosis to facilitate the early detection of diastolic dysfunction, which is instrumental in mitigating and delaying the onset and progression of heart failure, holding significant clinical relevance.MethodsThis research enrolled 556 patients suspected of experiencing Acute Coronary Syndrome (ACS) and stratified them into Groups A, B, C, and D according to the severity of coronary artery stenosis. The diastolic function of the left ventricle was indicated by the relaxation time constant, denoted as T value, which measures the temporal span from the peak rate of left ventricular pressure rise (dp/dt) to the end-diastolic pressure.ResultsThe T value of the left ventricle demonstrated a significant correlation with the Gensini Score and the T values across various peripheral arteries (P < 0.01). Pearson correlation analysis showed that the average value of peripheral arterial compliance indices in Group C and the average value of peripheral arterial compliance indices in Group D had a significant correlation with LV-T. At the same time, linear analysis of the average values of peripheral arterial compliance indices in both groups revealed that the average compliance indices in Groups C and D had a linear correlation with their LV-T (P < 0.05).When coronary artery stenosis exceeds 50%, the changes in peripheral arterial T values are significantly correlated with changes in LV-T.ConclusionsWhen coronary artery stenosis exceeds 50%, there is a decrease in peripheral artery compliance, showing a positive correlation with changes in left ventricular diastolic function. Measuring this compliance might offer an early diagnostic tool for assessing diastolic function.